Modelagem e simulação combinada com a metodologia lean seis sigma para melhoria de processos - Benassi, Adriano de Almeida (2023)
This dissertation presents a model for implementing process improvement in the industrial area in order to obtain better results, reduce waste, improve quality and operational efficiency, with monitoring and control of the main manufacturing indicators. As an objective, this dissertation seeks, from a brief theoretical foundation, to present the concepts, methods, procedures of the stages and quality tools and statistics proposed in Lean Six Sigma, combined with the Modeling and Simulation techniques, as an integrated system in the Modeling and Simulation Lean Six Sigma method. A framework is proposed, defining the methodological stages and steps of a roadmap for the application of Modeling and Simulation Lean Six Sigma. Subsequently, results of work on process improvement are presented, both applied and implemented in a multinational industry in the auto parts segment, using pure Lean Six Sigma methodology and later, using the proposed method Modeling and Simulation Lean Six Sigma, in a research- action, comparing the operating results, advantages and benefits that the practice, in combination, can offer Managers. Finally, a brief discussion was presented, which proves that using Lean Six Sigma with Modeling and Simulation can bring advantages and benefits when compared to the traditional method, which makes use of pure Lean Six Sigma.